Experimental investigation of the noise radiated by a ducted air flow discharge though diaphragms and perforated plates. (28th April 2020) - Laffay, P.; Moreau, S.; Jacob, M.C.; Regnard, J.
Abstract: An experimental investigation of the noise radiated by a ducted high pressure flow discharge through diaphragms and perforated plates is carried out for a large range of subsonic and supersonic operating conditions (Nozzle Pressure Ratio (NPR) from 1.2 to 3.6). A parametric study of the geometrical parameters is also conducted to characterize their influence on the acoustic radiation. This covers configurations from single diaphragms to multi-perforated plates with variable hole diameters and arrangements that are placed inside a cylindrical duct. Compared with the free discharge analysed in a first part of the study (perforated plates placed directly at the output of the duct), the discharge into a duct, which is closer to the practical applications, generates strong acoustic modifications. As expected, the broadband noise is disturbed by strong modulations due to acoustic resonances in the output duct (longitudinal resonances and transversal duct modes). However, as in the free configuration, a strong effect of the plate geometries on the mixing noise is observed, allowing to adapt or reduce this source. In particular, the increase of the ratio between the perforation spacing and the perforation diameter allows reducing the maximum amplitude of the mixing noise. Compared to the free-field discharge, the Sound Pressure Level (SPL) in the ducted configuration is on average proportional to the 6-th power of the velocity instead of the 8-th power. Moreover, there are two dominant frequency humps in the sound spectra. The low frequency one is characterized by a constant Helmholtz number, suggesting that the sound is shaped by the duct geometry, whereas the high frequency one is characterized by a constant Strouhal number suggesting that the sound is directly generated by the flow. Finally, for supersonic operating points, the screech radiation appearing with diaphragms in the free configuration is suppressed when the output duct is added but new high amplitude and low frequency tones appear for the largest diaphragms and perforated plates. These lines are due to a coupling between normal shock oscillations and longitudinal resonances.